2017
DOI: 10.18632/oncotarget.16847
|View full text |Cite
|
Sign up to set email alerts
|

Migration pattern, actin cytoskeleton organization and response to PI3K-, mTOR-, and Hsp90-inhibition of glioblastoma cells with different invasive capacities

Abstract: High invasiveness and resistance to chemo- and radiotherapy of glioblastoma multiforme (GBM) make it the most lethal brain tumor. Therefore, new treatment strategies for preventing migration and invasion of GBM cells are needed. Using two different migration assays, Western blotting, conventional and super-resolution (dSTORM) fluorescence microscopy we examine the effects of the dual PI3K/mTOR-inhibitor PI-103 alone and in combination with the Hsp90 inhibitor NVP-AUY922 and/or irradiation on the migration, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…Recent studies indicate that the HSP90 inhibitors 17-AAG and AUY922 also can affect cancer cell motility and migration (31)(32)(33)(34). To investigate whether these effects translate to onalespib, the effects of cisplatin and/or onalespib on migration and wound healing were investigated in two separate migration assays (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that the HSP90 inhibitors 17-AAG and AUY922 also can affect cancer cell motility and migration (31)(32)(33)(34). To investigate whether these effects translate to onalespib, the effects of cisplatin and/or onalespib on migration and wound healing were investigated in two separate migration assays (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, patients with GBM currently have a median survival of only 15 mo (Parsons et al 2008;Weller et al 2015;Ostrom et al 2016). This poor prognosis is due, in part, to the diffusive invasive growth of GBM cells, which prevents the possibility of complete resection and limits the effect of local radiotherapy (Naumman et al 2013;Memmel et al 2017). Poor prognosis can also be attributed to large inter-and intratumoral heterogeneity, wherein tumor subpopulations associated with different molecular characteristics develop resistance to radiation and chemotherapies (Liu et al 2018;Akgül et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest a novel timescale that can be targeted by parallel anti-migratory drugs, especially those that have reversible action such as certain cytochalasins [49,50], during radiotherapy and chemotherapy. Interestingly, anti-migratory drugs have recently been suggested by others for the improvement of radiotherapy [17,25] and chemotherapy [51,52]. Based on our results, the first 24 to 48 hours should be prime time to use the anti-migratory strategies.…”
Section: Timescales In Alteration Of Migration Reversible Interventimentioning
confidence: 60%
“…Several studies have since then been carried out to document the effects of radiotherapy on cancer cell migration and extensive reviews of these have been done [4,5]. Majority of the results showed that ionizing radiation enhanced the migration of cancer cells including GBM [21,[24][25][26]. A few cases [27,28] of purportedly reduced migration were included in the review [5] but it turns out that one of these [28] actually reported radiation-induced enhancement of migration and not reduction.…”
Section: Introductionmentioning
confidence: 99%